Perceived Expectation of ‘KIM YOUNG-RAN ACT’: An Application of the Theory of Planned Behavior (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study examines the effect of perceived expectation of the enactment of 'Kim Young-Ran Act' on intention to behave improper solicitation. The present work is framed with the Theory of Planned Behavior (TPB) to predict behavioral intention to commit solicitation. The target sample (N=291) was among an adult group aged of 30 to 60 years. Seventeen questionnaire items were designed to measure the constructs of the conceptual model. Demographic variables were controlled for by including age and gender. The results from a hierarchical multiple regression reveal that, (1) the model accounted for 26.8% of the total variance of intention and (2) attitude, subjective norm, perceived expectation of the enactment were significant independent predictors of behavioral intention to commit improper solicitation.